The Use of Nearpod Interactive Learning Media on Student Learning Motivation in Reading Skills at Mts Al-Rifa'ie 2 School - Jundana, Faris Haritsah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to examine the effect of Nearpod interactive learning media on students' learning motivation in reading ability at MTs Al-Rifa'ie 2. Nearpod was chosen for its ability to offer innovative features, including digital content, formative evaluation, and collaborative activities, which have great potential in increasing student engagement as well as creating a more interesting and meaningful learning experience. This study adopted a quantitative approach with an experimental design (or quasi-experiment if not fully randomized). Participants were divided into two groups: an experimental group that used Nearpod in the learning process, and a control group that was taught using conventional methods. Data was collected through a questionnaire on students' learning motivation in reading skills, which was administered both before (pre-test) and after treatment (post-test). The results clearly show that the use of Nearpod successfully increased students' learning motivation significantly, and this increase in motivation is positively correlated with the improvement of their reading ability. The significant value obtained was 0.001 (